(untitled) (Dhaka Shishu (Children) Hospital Journal, 2021)
Subclinical hypothyroidism is defined as serum levels of TSH above the upper limit of the reference range in the presence of normal concentrations of total T4 or free T4. This biochemical profile might be an indication of mild hypothyroidism, with a potential increased risk of metabolic abnormalities and cardiovascular disease among adults. Whether subclinical hypothyroidism results in adverse health outcomes among children is a matter of debate and so management of this condition remains challenging. Mild forms of untreated subclinical hypothyroidism do not seem to be associated with impairments in growth, bone health or neurocognitive outcome. However, ongoing scientific investigations have highlighted the presence of subtle proatherogenic abnormalities among children with modest elevations in their TSH levels. Although current findings are insufficient to recommend levothyroxine treatment for all children with mild asymptomatic forms of subclinical hypothyroidism, they highlight the potential need for assessment of cardiovascular risk among children with this condition. Increased understanding of the early metabolic risk factors associated with subclinical hypothyroidism in childhood will help to improve the management of affected individuals. DS (Child) H J 2020; 36(2): 146-151